التماميـّة الفنيـّة - ناصر, بشير مطيع (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
يهدف البحث في التمامية الفنية (Artistic Entirety) إلى القبض على بواعث غياب الفن في حياتنا المعيشة ، إذ يجد البحث أن جوهر هذا الغياب وفقدان الفعالية يكمن في تشتت للعملية الفنية واجتزائها بوصفها كائناً عضوياً يمارس حياته الكلية عبر حركية الحياة . وفي سبيل ما يصبو إليه البحثُ ، اقتضى بنا الأمر الإحاطة بسائر أبعاد العملية الإبداعية وجدليتها معاً فالخلل في مهمة الفن يؤدي إلى خلل في الماهية . ولما كان العمل هو جوهر التمامية الفنية كما هوجوهر الحياة ، فان الجمال التمامي قائم على الانسجام المتحرك ، على خلاف الكمالية ، أو الكمال السكوني المنجز . وتأسيساً عليه تغدو التمامية في وحدة المتخالف ، أو شدة الائتلاف من شدة الاختلاف . This article, which deals with the artistic entirety, aims at pointing out the reasons behind the Absence of art in our daily life. The essential reason of this absence, and consequently the absence of action, lies in the dissipation and disconnection of the artistic process which is an organic entity practicing its entire life through the motion of life. The goal of the article made it necessary for in to deal with all aspects and problems of the artistic process. Therefore any malfunction in the task of art leads to malfunction in the essence (of art) and since action is the essence of artistic entirety, as well as of life, the aesthetics of artistic entirety depends upon moving harmony, contrary to motionless perfection. Thereupon the artistic entirety resides is the metric of contradictions or in the harmony resetting from items dissimilarity.